Respuesta :
Answer:
Step-by-step explanation:
To prove 7 divides [tex]2^{n+1} +3^{2n-1}[/tex]
let [tex]P\left [ n\right ]=2^{n+1} +3^{2n-1}[/tex]
for n>1
For n=1 [tex]2^{1+1} +3^{2-1}=7 \left ( divisible by 7\right )[/tex]
to show that [tex]P\left ( n+1\right )=P\left ( n\right )[/tex]
[tex]2^{n+1} +3^{2n-1}=7x [/tex] for some interger x
this equation will also be valid for [tex]P\left [ n+1\right ]=2^{\left ( n+1\right )+1}+3^{2\left ( n+1\right )-1}[/tex]
[tex]P\left [ n+1\right ]=2^{\left ( n+1\right )+1}+3^{2n+1}[/tex]
rearranging
[tex]P\left [ n+1\right ]=2\dot 2^{n+1} +3^2\dot 3^{2n-1}[/tex]
[tex]P\left [ n+1\right ]=2\dot 2^{n+1} +9\dot 3^{2n-1}[/tex]
[tex]P\left [ n+1\right ]=2\dot 2^{n+1} +\left ( 7+2\right )\dot 3^{2n-1}[/tex]
[tex]P\left [ n+1\right ]=2\dot 2^{n+1} +\left ( 7\right )\dot 3^{2n-1}+\left ( 2\right )\dot 3^{2n-1}[/tex]
[tex]P\left [ n+1\right ]=2\dot \left ( 2^{n+1} +3^{2n-1}\right )+\left ( 7\right )\dot 3^{2n-1}[/tex]
[tex]P\left [ n+1\right ]=2\dot P\left ( k\right )+\left ( 7\right )\dot 3^{2n-1}[/tex]
using induction hyposthesis
[tex]2^{n+1} +3^{2n-1}=7x [/tex]
thus
[tex]P\left [ n+1\right ]=2\dot 7x +\left ( 7\right )\dot 3^{2n-1}[/tex]
[tex]P\left [ n+1\right ]=7\left ( 2x+3^{2n-1}\right )[/tex]
hence 7 divides [tex]2^{n+1} +3^{2n-1}[/tex]